Предмет: Химия,
автор: Аноним
CA→CA(OH)2→CA3(PO)4→CA(OH)2→CA(NO3)2
Ответы
Автор ответа:
0
Ca+2H2O=Ca(OH)2+H2
3Ca(OH)2+2H3PO4=Ca3(PO4)2+6H2O
Ca3(PO4)2+6NaOh=3Ca(OH)2+2Na3PO4
Ca(OH)2+2HNO3=Ca(NO3)2+2H2O
3Ca(OH)2+2H3PO4=Ca3(PO4)2+6H2O
Ca3(PO4)2+6NaOh=3Ca(OH)2+2Na3PO4
Ca(OH)2+2HNO3=Ca(NO3)2+2H2O
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Jasmine3412
Предмет: Другие предметы,
автор: Аноним
Предмет: Биология,
автор: Davleon321
Предмет: Математика,
автор: urdikhan
Предмет: Математика,
автор: komanda2016Metelyak